Cytomegalovirus Retinitis Screening and Treatment in Human Immunodeficiency Virus Patients in Malawi: A Feasibility Study. (6th November 2019) - Ocieczek, Paulina; Barnacle, James R; Gumulira, Joe; Phiri, Sam; Heller, Tom; Grabska-Liberek, Iwona
Abstract: Background: Cytomegalovirus retinitis is a treatable cause of blindness in people with human immunodeficiency virus (HIV) typically with CD4 counts <50 cells/mm 3 . Diagnosis is with indirect fundoscopy, and treatment is with intravitreal ganciclovir injections or systemic therapy. However, diagnosis and treatment are not widely available in Malawi, which has an adult HIV prevalence estimated at 10.6%. This study aimed to establish the prevalence of cytomegalovirus retinitis among people with HIV in Malawi and the feasibility of screening. Methods: Patients with CD4 counts <200 cells/mm 3 were examined from 2 HIV clinics in Lilongwe and the main government hospital. Data were collected on antiretroviral therapy, ocular symptoms, and visual acuity. Fundoscopy was performed to investigate for features of cytomegalovirus retinitis. Retinal photographs were reviewed by an ophthalmologist. Patients diagnosed with cytomegalovirus retinitis were offered weekly ganciclovir injections, because systemic treatment was not available. Results: Five of the 102 people with HIV screened had cytomegalovirus retinitis (4.9%). All affected patients had CD4 counts <50 cells/mm 3 (mean, 15 cells/mm 3 ; range, 3–22 cells/mm 3 ). Visual acuity was unhelpful in identifying those with cytomegalovirus retinitis. Symptomatically, only blurred vision was useful. Two patients consented to treatment, 1 of which improved but relapsed after defaulting. Conclusions: Cytomegalovirus retinitis screening based on CD4 count is essential to early recognition because visual acuity and symptoms are unreliable. Cytomegalovirus retinitis is a significant yet neglected public health issue in Malawi. Oral valganciclovir is essential to reduce blindness and mortality in those diagnosed but is not yet available. Further screening and advocacy are needed. Abstract : Despite an estimated cytomegalovirus retinitis prevalence in people with HIV in Malawi, the logistics and acceptability of intravitreal injections and financial impact on patients hinder treatment. Further data, oral valganciclovir, and strong advocacy are needed to reduce future morbidity/mortality.